A pilot study evaluating the safety and CD34+ cell mobilizing activity of escalating doses of plerixafor in healthy volunteers - Lemery, Steven J.; Hsieh, Matthew M.; Smith, Aleah; Rao, Sheila; Khuu, Hanh M.; Theresa, Donohue; Viano, Jennifer M.; Cook, Lisa; Goodwin, Rose; Boss, Carol; Calandra, Gary; Geller, Nancy; et al. (British journal of haematology, 2011)
Summary This study evaluated the safety and CD34+ cell mobilizing activity of escalating doses of plerixafor in healthy volunteers. Three cohorts of six subjects received two different doses of plerixafor separated by at least 2 weeks to allow for adequate pharmacodynamic wash‐out. The following dosing cohorts were evaluated: 0·24 and 0·32 mg/kg (Cohort 1); 0·32 and 0·40 mg/kg (Cohort 2); and 0·40 and 0·48 mg/kg (Cohort 3). Circulating CD34+ cells were measured 0, 2, 4, 6, 8, 10, 12, 14, 18 and 24 h after each dose. Blood colony‐forming units were measured at baseline and 6 h after each dose. Common adverse events were diarrhoea, injection site erythema, perioral numbness, sinus tachycardia, headache, nausea, abdominal distention and injection site pain. No dose limiting toxicities occurred. When higher doses of plerixafor were administered, there was a trend towards higher peak CD34+ counts and CD34+ area under the curves, although these differences did not achieve statistical significance, perhaps due to intra‐subject variability. Together, these data show that the higher doses of plerixafor evaluated in this study are reasonably safe and suggest that a larger study should be performed to definitively answer whether increased numbers of CD34+ cell are mobilized with higher doses of plerixafor.